sports The role of sports clubs and associations in the city of Batna in attracting and accompanying children with autism spectrum disorder - Younes, Ahmed Imad Eddine; Kadri, Abdelhafidh (sports creativity, 2025)
( This study aimed to determine the role of active sports clubs and associations in the state of Batna and their contribution to attracting and integrating children with autism spectrum disorder into sports practice, and the availability of qualified and specialized staff to accompany this sample of children. In this study, we relied on the descriptive and analytical methodology, and a random sample of 35 clubs was selected from various competitive and recreational sports activities, and the study questionnaire was distributed to them, where we recorded a significant deficiency or near absence of activity for children with autism spectrum disorder in these clubs, and it was also recorded There is a severe shortage of specialists in dealing with this sample in sports clubs and associations.